AdaDerivative optimizer: Adapting step-sizes by the derivative term in past gradient information. (March 2023) - Zou, Weidong; Xia, Yuanqing; Cao, Weipeng
Abstract: AdaBelief fully utilizes "belief" to iteratively update the parameters of deep neural networks. However, the reliability of the "belief" is determined by the gradient's prediction accuracy, and the key to this prediction accuracy is the selection of the smoothing parameter β 1 . AdaBelief also suffers from the overshoot problem, which occurs when the value of parameters exceeds the value of the target and cannot be changed along the gradient direction. In this paper, we propose AdaDerivative to eliminate the overshoot problem of AdaBelief. The key to AdaDerivative is that the "belief" of AdaBelief is replaced by the derivative term's exponential moving average (EMA), which can be constructed as ( 1 − β 2 ) ∑ i = 1 t β 2 t − i ( g i − g i − 1 ) 2 based on the past and current gradients. We validate the performance of AdaDerivative on a variety of tasks, including image classification, language modeling, node classification, image generation, and object detection tasks. Extensive experimental results demonstrate that AdaDerivative can achieve state-of-the-art performance.